Experimental investigation of peat soil characteristics in Sarawak - Walter, Jaol (Universiti Malaysia Sarawak, UNIMAS, 2004)
Peat layers are scattered along the trace of Malaysia, especially in Sarawak (East Malaysia). They represent 13 percent of Sarawak’s land area and occupy about 1.66 million hectares. The abundance of peat soils in Sarawak made it a hectic and tedious job for the development of Sarawak especially in the rural area. The primary objective of this project is to determine the geotechnical properties of tropical peat soils in Sarawak. Peat soil samples are taken from Matang, Batu Kawa, and Kota Samarahan area. The experiment conducted consists of the degree of humification test, loss on ignition test, Atterberg limit test, particle density test, fibric content test, moisture content test, pH test, hydrometer test, standard Proctor test, and California bearing ratio (CBR) test. The result of experimental investigation postulates a high content of moisture, organic and fibric content of peat soil. Besides that, peat soil in Sarawak is categorized in hemic group, with pH value of 3.5 to 4.5 and CBR value of 2.5% to 3.3%. From the data and results of the findings, it may be used to generate a standard procedure to tackle problems regarding peat soil.